Convergence of meta-controlled Boltzmann machine and its application for bilevel programming problem - Nishiigami, Wataru; Watada, Junzo, Prof. Dr.; Shamshul Bahar, Yakoob, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.